The use of geographic information technologies in the study of sleeping tree selection by black and gold howler monkeys (Alouatta caraya) (Huellas, 2025)
Understanding distribution and spatial patterns is one of the core principles of Geography, applicable to both human and natural variables. Within this context, the application of Geographic Information Technologies provides a valuable tool for enhancing studies of species behaviors such as, in this case, the sleeping tree selection by black howler monkeys (Alouatta caraya) throughout the year. This study confirmed that a troop of monkeys located in a forest adjacent to San Cayetano Provincial Park (Corrientes, Argentina) tends to occupy larger trees and/or areas with greater vegetative volume. Considering the recorded sleeping sites and the corresponding meteorological conditions, it was concluded that the selection of these locations is primarily associated with the pursuit of climatic comfort, rather than driven by proximity to food sources or protection from predators.